An Annotated Translation from English into Indonesian: The Soul of the Indian by Charles Alexander Eastman - Noverdi, Trias (UI Scholars Hub, 2019)
This research is an annotated translation in which the researcher provides detailed explanation to account for his selection of translation equivalents. The data source in this research is The Soul of the Indian, a book by Charles Alexander Eastman. This study sought to identify problems encountered over the course of translation and offer the solutions thereto. The data for the study were derived from the problems thus identified and classified into categories of annotation. The qualitative method was employed using a comparative analysis translation model. The key findings of this research are twofold. First, out of 27 units of analysis, 8 are names of or designations for a God or Deity, 1 is the name of a ceremony, 1 is a designation for a spiritual figure, 1 is a name of a spiritual practice, 4 are figures of speech, 9 involve specific terms, and 3 are collocations. The translation itself employed 8 different procedures, with combined procedures being predominantly used. Second, the difficulties encountered when dealing with the problems were solved by employing relevant translation theories, methods, and procedures. These findings demonstrate that Indian spiritualism and culture are interrelated so that the annotation data obtained are not only spiritual in nature but also cultural. A translator should be knowledgeable not only about spiritualism, but also culture prevailing in both the source and target language communities.